System support for integrated ubiquitous computing environments - José, Rui (2003)
This paper describes an ongoing research on the issues of interoperability and seamless integration between a global user environment and the ubiquitous computing environments corresponding to the physical locations visited by that user. The novel concept of Value ADded Environment (Vade) is introduced as an administrative and physical domain, where the locally available facilities can be combined with the external home environments of users within its boundaries to enable an integrated and enhanced functionality. The main goal of our work is to allow generic applications to access and benefit from resources and context information that are normally only available to applications created specifically for a particular ubiquitous computing environment. Our preliminary results, highlight a number of key integration issues and show a possible path for the convergence between ubiquitous computing research and mobile services.